Effect of innovative vs. usual care physical therapy in subacute rehabilitation after stroke. A multicenter randomized controlled trial - Sivertsen, Marianne; Arntzen, Ellen Christin; Alstadhaug, Karl Bjørnar; Normann, Britt (Frontiers in Rehabilitation Sciences, 2022)
Background Research on stroke rehabilitation often addresses common difficulties such as gait, balance or physical activity separately, a fragmentation contrasting the complexity in clinical practice. Interventions aiming for recovery are needed. The purpose of this study was to investigate effects of a comprehensive low-cost physical therapy intervention, I-CoreDIST, versus usual care on postural control, balance, physical activity, gait and health related quality of life during the first 12 weeks post-stroke. Methods This prospective, assessor-masked randomized controlled trial included 60 participants from two stroke units in Norway. Participants were randomized to I-CoreDIST (n=29) or usual care physical therapy (n=31), received 5 sessions/week when in-patient or 3 sessions/week as out-patients. Primary outcomes were the Trunk Impairment Scale-modified Norwegian version (TISmodNV) and activity monitoring (ActiGraphsWgt3X-BT). Secondary outcomes were the Postural Assessment Scale for Stroke, MiniBesTEST, 10-meter walk test, 2-minute walk test, force-platform measurements and EQ5D-3L. Stroke specific quality of life scale was administered at 12 weeks. Linear regression and non-parametric tests were used for statistical analysis. Results Five participants were excluded and seven lost to follow-up, leaving 48 participants in the intention-to-treat analysis. There were no significant between-group effects for primary outcomes: TIS-modNV (p=0,857); daily average minutes of sedative, (p=0.662), light (p=0.544), moderate activity (p=0.239) and steps p=0.288 or secondary outcomes at 12 weeks except for significant improvements on EQ5D-3L in the usual care group. Within-group changes were significant for all outcomes in both groups except for activity levels that were low, EQ5D-3L favoring the usual care group and force-platform data favoring the intervention group. Conclusions Physical therapy treatment with I-CoreDIST improved postural control, balance, physical activity and gait during the first 12 weeks after a stroke but is not superior to usual care.